2006
DOI: 10.1111/j.1460-9568.2006.04801.x
|View full text |Cite
|
Sign up to set email alerts
|

Prominent corticosteroid disturbance in experimental prion disease

Abstract: Prion diseases comprise a group of neurodegenerative disorders that invariably lead to death in affected individuals. The most prominent event in these diseases is a rapid and pronounced neuronal loss, although the cause and the precise mechanisms of neuronal cell death have not been identified so far. Recently, it has been suggested that corticosteroids might play a role in the pathogenesis of neurodegenerative disorders in general, as the regulation of these hormones was found to be disturbed in Alzheimer's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 50 publications
5
16
0
Order By: Relevance
“…The method of noninvasive stress measurement has been successfully validated and applied several times in mice [18][19][20][21][22]. In accordance with the results of Touma et al [23], a clear diurnal rhythm of corticosterone metabolite levels was observed, but in the present study, a strong variation of individual measurements was also observed in all groups.…”
Section: Reuse Of Foster Mothers For Embryo Transfersupporting
confidence: 93%
See 1 more Smart Citation
“…The method of noninvasive stress measurement has been successfully validated and applied several times in mice [18][19][20][21][22]. In accordance with the results of Touma et al [23], a clear diurnal rhythm of corticosterone metabolite levels was observed, but in the present study, a strong variation of individual measurements was also observed in all groups.…”
Section: Reuse Of Foster Mothers For Embryo Transfersupporting
confidence: 93%
“…2). During this period, the mice were housed on cotton sheets instead of wood bedding as described previously [19] with minor modifications. Samples were frozen (À208C) and analyzed using a 5a-pregnane-3b,11b,21-triol-20-one enzyme immunoassay as described in detail by Touma et al [20,21].…”
Section: Stress Evaluation By Noninvasive Corticosterone Measurementmentioning
confidence: 99%
“…These alterations include altered circadian activity rhythms and sleep activities (Tobler et al, 1996), deficits in hippocampal-dependent spatial learning (Criado et al, 2005), altered stress response and neuroendocrine stress functions (Sanchez-Alavez et al, 2007), altered fear-induced behavior (Lobao-Soares et al, 2008), and disregulation of the hypothalamic-pituitary-adrenal axis, the ''stress'' axis (Sanchez-Alavez et al, 2008). Intriguingly, pathological alterations that can be related to a dysfunction of the thalamolimbic system have been described also in some cases of prion diseases, such as corticosteroid disturbance (Gayrard et al, 2000;Voigtlander et al, 2006). Moreover, patients suffering the genetic prion disease FFI show predominant sleep, neuroendocrine, and autonomic dysfunction (Montagna et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Chronic infection by Mycobacterium tuberculosis in humans, however, leads to increased glucocorticoids [43], possibly mediated by cytokine activation of the HPA axis during the immune response to infection [8,9,41]. Further, increases in FGMs have been detected in mice innoculated with mouse scrapie as the disease approaches late stage [49]. Thus, although glucocorticoids are often implicated in immuno-suppression, they may also be altered in response to parasitism [25] and this positive feedback may result in ''vicious circles'' of susceptibility, infection and transmission within an individual and within a social group or population [6].…”
Section: Discussionmentioning
confidence: 99%